Hippocampal Damage Disrupts Eyeblink Conditioning in Mice Lacking Glutamate Receptor Subunit δ2 - Takatsuki, K. (Kluwer Academic Publishers, 2002)
Cerebellar long-term depression (LTD) at the parallel fiber-Purkinje cell synapses has been proposed to be a neural substrate for classical eyeblink conditioning. Mutant mice lacking the glutamate receptor subunit δ2 (GluRδ2), in which the cerebellar LTD is disrupted, exhibited a severe impairment in the delay eyeblink conditioning with a temporal overlap of CS and US. However, they learned normally trace and delay conditioning without CS-US overlap, suggesting a learning mechanism which does not require the cerebellar LTD.In the present study, we tested possible involvement of the hippocampus in this cerebellar LTD-independent learning. We examined effects of scopolamine and hippocampal lesion on the delay conditioning without CS-US overlap. TheGluRδ2 mutant mice that received scopolamine or aspiration of the dorsalhippocampus together with its overlying cortex exhibited a severe impairment in learning, while the control mutant mice that received saline or aspiration of the overlying cortex learned normally. In contrast, wild-type mice that received either treatment learned as normally as the control wild-type mice. These results suggest that the hippocampus is essential in the cerebellar LTD-independent learning in the GluRδ2 mutant mice, indicating a newrole of hippocampus in the paradigm with a short trace interval.